Aquisição do Português escrito: coesão e coerência na construção de um texto de uma aluna surda - PANTOJA, Gizelle Barbosa (2019)
This paper has the purposes of describing and analysing issues related to cohesion and coherenses in the writing of a deaf student girl of public and democratic school who lives in the Igarapé-Miri/Pa city. This research take the forms of corpus method based on qualitative approach. The corpus is made by a latter produced by mentioned student during the portuguese language's classes by the time of Supervised Training, compulsory discipline of the graduation in Libras e Portuguese as second language.